The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1038/sj.bjc.6602350
|View full text |Cite
|
Sign up to set email alerts
|

Luteinising hormone-releasing hormone analogue reverses the cell adhesion profile of EGFR overexpressing DU-145 human prostate carcinoma subline

Abstract: Cetrorelix, a luteinising hormone-releasing hormone (LHRH) analogue, has been shown to limit growth of the human androgenindependent prostate cell line DU-145, although other inhibitory actions may also be affected. Both growth and invasion of DU-145 cells are linked to autocrine epidermal growth factor receptor (EGFR) signalling. Invasiveness requires not only cells to migrate to conduits, but also reduced adhesiveness between tumour cells to enable separation from the tumour mass. Thus, we investigated wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 80 publications
(95 reference statements)
5
41
0
1
Order By: Relevance
“…This suggested that autocrine EGFR signalling present in prostate carcinomas may contribute to E-cadherin repression in these tumours. This was supported by our recent finding that pharmacological abrogation of EGFR signalling in prostate carcinoma cells reverses decreased E-cadherin expression rendering these cells less invasive and more cohesive (Jawhari et al, 1999;Yates et al, 2005). This re-expression of E-cadherin is similarly observed by close contacts of DU-145 prostate carcinoma cells when cultured within the liver microenvironment (Yates et al, 2007).…”
supporting
confidence: 74%
See 3 more Smart Citations
“…This suggested that autocrine EGFR signalling present in prostate carcinomas may contribute to E-cadherin repression in these tumours. This was supported by our recent finding that pharmacological abrogation of EGFR signalling in prostate carcinoma cells reverses decreased E-cadherin expression rendering these cells less invasive and more cohesive (Jawhari et al, 1999;Yates et al, 2005). This re-expression of E-cadherin is similarly observed by close contacts of DU-145 prostate carcinoma cells when cultured within the liver microenvironment (Yates et al, 2007).…”
supporting
confidence: 74%
“…As this was reminiscent of the situation with LHRH receptor transmodulation of autocrine EGFR signalling in DU-145 cells (Yates et al, 2005), we asked whether a similar situation might be functioning in this setting. We expressed the PKC transmodulation-resistant EGFR A654 variant (Welsh et al, 1991) in the DU-145 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are always overexpressed in malignant tumors and are thought to contribute to tumor progression (34,35). Yates and colleagues (36,37) found that in vitro inhibition of autocrine EGFR signaling increased E-cadherin expression and cell-cell heterotypic adhesion and that E-cadherin upregulation was prevented by expressing a downregulation-resistant EGFR variant. E-cadherin and catenins, but not activated EGFR, were also found in human prostate cancer metastases to the liver, supporting the notion that the inverse relationship between E-cadherin expression and EGFR also exists in de novo human tumors (36).…”
Section: Mechanism Of Metmentioning
confidence: 99%